The Complexity of Complex Developmental Trauma: A Proposal from the Attachment & Complexity Model (Mac) - Guajardo-Sainz, H; Kushner-Lanis, D; Lecannelier-Acevedo, F (REVISTA PSIQUIATRIA & PSICOLOGIA HUMANISTA, S L, 2021)
Actual proposals about infant trauma seek to explain the process which can understand the organization of the experience and the style of functioning of the many children who suffers multiple, chronic, and interpersonal pain, especially during the most important period of human development (0 to 5). This proposal has been headed under the name of "Complex Developmental Trauma", and has made majors advances in the understanding, explanation, and treatment of this atrocious phenomena, through multi-level and multi-discipline approaches. However, we think that Complex Trauma can made more and better advances in the areas of explaining (and intervening) it if paradoxically can take the input of the whole area of Complex System approach, chaos theory, combined with the recent developments in the psychobiology of attachment, evolutionary perspectives on human nature and human mind(such as the comprehension of hunter-gatherer evidences), and the embodiment of human action and cognition. The present paper made some initials proposals considering the areas already mentioned under a model called "Attachment and Complexity Model", which we humble considered a paradigmatic in understanding development, "psychopathology", and intervention modalities.